THE USE OF PERENNIAL VINES FOR VERTICAL LANDSCAPING IN THE LANDSCAPING OF THE CITY OF SAMARKAND - Shukurova, M.E.; Ravshanova, E.Z. (SCIENCE and SOCIETY, 2025)
It was noticed that the studied species of liana in tropical and temperate climates exhibit features characteristic of the region. In the conditions of the Samarkand region, an increase in air temperature leads to a decrease in soil moisture. To do this, it is desirable to constantly monitor humidity and temperature in areas where liana species are planted. The studied species of liana reproduce well mainly by seeds and cuttings with high germination. Hedera helix is widely used in the landscaping of the city of Samarkand, mainly because of its evergreenness and longevity during the four seasons of the year.